ESCALATING ORGANIZATIONAL PERFORMANCE IN DA'WAH: THE TRANSFORMATION OF HUMAN RESOURCE MANAGEMENT - M. Fahmi Ashari; M. Firdaus; Cecep Castrawijaya; Silky Sabella Maharani (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2024)
This research aims to understand the relationship between Human Resource Management and the Performance of Da'wah Organizations (Case Study: Nahdlatul Ulama. The research method uses qualitative research with the type of case study on Nahdlatul Ulama. The technique for obtaining data uses library research. The results of this research are that Nahdlatul Ulama has a good organizational structure, from management levels and a complete management structure. In implementing human resources in the Nahdlatul Ulama organization, it is realized in the form of priority work programs that lead to human resource management, first, development programs human quality which focuses on 2 aspects, namely the education and health aspects. The education aspect is realized in the NU Scholarship program by Lakpesdam PBNU and the health aspect is realized in the form of the Inclusion Program and Gerakan Keluarga Maslahat NU (GKMNU) and the second priority work program, namely organizational strengthening. institutions and networks, which are realized in one form of activity, namely cadre formation. Furthermore, the relationship between human resource management and the performance of missionary organizations has a very close relationship in managing, organizing and utilizing human resources so that they can contribute to the performance of missionary organizations.